2020
DOI: 10.1186/s13071-020-3970-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional changes in Toxoplasma gondii in response to treatment with monensin

Abstract: Background: Infection with the apicomplexan protozoan parasite T. gondii can cause severe and potentially fatal cerebral and ocular disease, especially in immunocompromised individuals. The anticoccidial ionophore drug monensin has been shown to have anti-Toxoplasma gondii properties. However, the comprehensive molecular mechanisms that underlie the effect of monensin on T. gondii are still largely unknown. We hypothesized that analysis of T. gondii transcriptional changes induced by monensin treatment can rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…These results suggest that parasite inhibition may have been achieved through dysregulation of the biosynthesis of key nutrients in the host cells and/or inhibition of nutrient transport between cell organelles, limiting their transport into parasitophorous vacuole. This finding is consistent with a previous transcriptomic study of monensin-treated porcine kidney (PK)-15 cells, which revealed an overrepresentation of the downregulated genes involved in the biosynthesis of spliceosome, ribosome, and protein processing in ER, suggesting that monensin, via down-regulation of protein biosynthesis, can limit the parasite growth and proliferation [41].…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that parasite inhibition may have been achieved through dysregulation of the biosynthesis of key nutrients in the host cells and/or inhibition of nutrient transport between cell organelles, limiting their transport into parasitophorous vacuole. This finding is consistent with a previous transcriptomic study of monensin-treated porcine kidney (PK)-15 cells, which revealed an overrepresentation of the downregulated genes involved in the biosynthesis of spliceosome, ribosome, and protein processing in ER, suggesting that monensin, via down-regulation of protein biosynthesis, can limit the parasite growth and proliferation [41].…”
Section: Discussionsupporting
confidence: 93%
“…However, these genes were then upregulated after 4 h of treatment in the E. tenella- resistant strain. Different results were observed in the T. gondii RH strain, cytoskeletal and transmembrane proteins were differently expressed in the monensin-resistant strain determined by proteomics (Thabet et al, 2018 ), and the other study showed that protein biosynthesis-related pathways (spliceosome, ribosome, and protein processing in the endoplasmic reticulum) were downregulated in T. gondii RH strain in response to 24 h of monensin treatment (Zhai et al, 2020 ). These results suggest that monensin treatment affects parasite protein synthesis and may have different effects on different parasite stages (e.g., sporozoites and tachyzoites).…”
Section: Discussionmentioning
confidence: 98%
“…Lavine and Arrizabalaga (Lavine and Arrizabalaga, 2011 ) highlighted that canonical histones were significantly upregulated in T. gondii after 24 h of exposure to monensin, suggesting that monensin alters the cell cycle of the parasite. More recently, Zhai et al ( 2020 ) showed that protein biosynthesis-related pathways were significantly downregulated in T. gondii after monensin treatment. Quantitative proteomic analysis was also used to understand the differences in gene expression between E. tenella -sensitive and -resistant strains (Thabet et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in our previous study that TR in T. gondii is an essential virulence effector with antioxidant function, which is critical for parasite growth and survival ( Xue et al, 2017 ). Moreover, in-depth studies of T. gondii antioxidant-related genes may provide a theoretical basis for developing anti- T. gondii drugs because some currently available drugs (such as monensin, mefloquine, and artemisinin) that induce ROS production and target the antioxidant system have been shown to be effective against T. gondii and/or Plasmodium ( Berens et al, 1998 ; Charvat and Arrizabalaga, 2016 ; Gunjan et al, 2016 ; Zhai et al, 2020 ). Therefore, identification parasite antioxidant genes is important for understanding the mechanisms of T. gondii in eliminating ROS, as well as for identifying useful targets for anti- Toxoplasma drugs, and this requires further investigations.…”
Section: Discussionmentioning
confidence: 99%